2008
DOI: 10.3324/haematol.11661
|View full text |Cite
|
Sign up to set email alerts
|

18-F FDG-PET in the staging of lymphocyte-predominant Hodgkin's disease

Abstract: This bicentric study assessed retrospectively the usefulness of 18 F-FDG-PET in the staging of 31 patients with lymphocyte-predominant Hodgkin's disease (LPHD). FDG-PET and conventional explorations (CE) were performed for initial disease (n=25) or recurrence (n= 6). All the 68 involved sites were detected by PET including 5 extra-nodal lesions. Only 43 nodal sites (68%) and one splenic focus were detected by CE. PET changed staging in 9 patients (7 upstaged, 2 downstaged) and radiation fields in 3 patients. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
(11 reference statements)
2
15
0
Order By: Relevance
“…This tool is now the standard for staging and evaluating the treatment response and detecting the aggressiveness of the disease. Recently, it has been proposed to guide the biopsies [5,6] to detect low-grade lymphoma transformation, which is associated with a higher SUV [4,7]. A similar result was reported concerning splenic SUV in low-grade non-Hodgkin’s lymphoma [8].…”
Section: Figsupporting
confidence: 66%
See 1 more Smart Citation
“…This tool is now the standard for staging and evaluating the treatment response and detecting the aggressiveness of the disease. Recently, it has been proposed to guide the biopsies [5,6] to detect low-grade lymphoma transformation, which is associated with a higher SUV [4,7]. A similar result was reported concerning splenic SUV in low-grade non-Hodgkin’s lymphoma [8].…”
Section: Figsupporting
confidence: 66%
“…The suggested cut-off value for the distinction between indolent and high-grade lymphoma, with 100% specificity, was 13, using a receiver operating characteristic (ROC) technique. In a large series of NLPHL, the median SUV was 6.1 (range, 1.2–20.1) [6]. No SUV data were available concerning an aggressive transformation.…”
Section: Figmentioning
confidence: 99%
“…Glucose uptake and metabolism in the tumor cells may, therefore, be less important in LP cells of NLPHL than in HRS cells of classical HL, as suggested by Hutchings et al, who, in a PET study, found significantly lower standardized glucose uptake values in NLPHL than in classical HL [13]. Nonetheless, a different study showed that staging by PET scan is applicable in NLPHL [30]. We observed GLUT1 expression in the reactive B cell infiltrate in lymphocyte rich HL subtypes (Figure 1f), while the T cell dominated areas were GLUT1-negative.…”
Section: Resultsmentioning
confidence: 99%
“…Positron emission tomography plays an important role in evaluation of Hodgkin lymphoma, for staging and therapeutic assessment [18, 19]. The PET scan has a prognostic value for evaluation of therapy [2022].…”
Section: Discussionmentioning
confidence: 99%